PERAN HUMAS DALAM PEMASARAN PENDIDIKAN DI SD NEGERI 160 PALEMBANG - Yumi Permata Sari; Ade Akhmad Saputra (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2026)
ABSTRACT Competition among educational institutions in the digital era requires elementary schools to optimize the role of public relations (PR) as an effective educational marketing strategy. However, many schools have not utilized digital media optimally, resulting in school image, reputation, and attractiveness that are not fully developed in the public eye. This condition indicates a gap between technological demands and the implementation of public relations functions within schools. This study aims to analyze the role of public relations in educational marketing at SD Negeri 160 Palembang. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation involving the principal and the vice principal for public relations as key informants. The findings reveal that public relations serves as an institutional communicator, a builder of a positive school image, a liaison between the school and the community, and a manager of publication media. In carrying out these roles, public relations utilizes social media, the school website, banners, and direct communication to disseminate information and strengthen public trust. In conclusion, public relations significantly contributes to enhancing the school’s image and public confidence through effective communication and the use of digital media. These findings highlight that optimizing digital-based public relations is a crucial strategy for improving competitiveness and sustaining educational marketing in elementary schools. ABSTRAK Persaingan antar lembaga pendidikan di era digital menuntut sekolah dasar mengoptimalkan peran hubungan masyarakat (humas) sebagai strategi pemasaran pendidikan yang efektif. Namun, masih banyak sekolah yang belum memanfaatkan media digital secara optimal sehingga citra, reputasi, dan daya tarik sekolah belum terbentuk secara maksimal di mata masyarakat. Kondisi ini menunjukkan adanya kesenjangan antara tuntutan perkembangan teknologi dan implementasi fungsi humas di lingkungan sekolah. Penelitian ini bertujuan menganalisis peran humas dalam pemasaran pendidikan di SD Negeri 160 Palembang. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi yang melibatkan kepala sekolah dan wakil kepala sekolah bidang humas sebagai informan utama. Hasil penelitian menunjukkan bahwa humas berperan sebagai komunikator lembaga, pembangun citra positif sekolah, penghubung antara sekolah dan masyarakat, serta pengelola media publikasi. Dalam menjalankan perannya, humas memanfaatkan media sosial, website sekolah, banner, dan komunikasi langsung untuk menyebarluaskan informasi serta meningkatkan kepercayaan publik. Kesimpulannya, humas berkontribusi signifikan dalam memperkuat citra sekolah dan membangun kepercayaan masyarakat melalui komunikasi yang efektif dan pemanfaatan media digital. Temuan ini menegaskan bahwa optimalisasi humas berbasis digital merupakan strategi penting untuk meningkatkan daya saing dan keberlanjutan pemasaran pendidikan di sekolah dasar.